Answer with Explanation:
We are given that
Mass of rider=m=77 kg
Mass of bike =m'=7.3 kg
Initial velocity,u=9.3 m/s
Final velocity,v=6 m/s
A.Change in velocity=v-u=6-9.3=-3.3 m/s
Total mass,M=m+m'=77+7.3=84.3 kg
Change in momentum=[tex]M(v-u)=84.3(-3.3)=-278.19 kgm/s[/tex]
B.Impulse=Ft=Change in momentum=-278.19kg m/s
C.Time,t=13.2 s
[tex]v=u+at[/tex]
Using the formula
[tex]6=9.3+13.2a[/tex]
[tex]13.2a=6-9.3=-3.3[/tex]
[tex]a=-\frac{3.3}{13.2}=-0.25 ms^{-2}[/tex]
F=[tex]ma[/tex]
[tex]F=84.3(-0.25)=-21.075 N[/tex]
D.[tex]S=ut+\frac{1}{2}at^2[/tex]
[tex]S=9.3(13.2)+\frac{1}{2}(-0.25)(13.2)^2[/tex]
[tex]S=100.98 m[/tex]